1989
DOI: 10.1111/j.1545-5300.1989.00399.x
|View full text |Cite
|
Sign up to set email alerts
|

The “Psychosomatic Family” Model: An Empirical and Theoretical Analysis

Abstract: Evolution of the Family Systems Paradigm has been constrained by the dichotomy between theory building and empirical research. This article integrates these two domains by presenting a theoretical analysis of the "psychosomatic family" model as it informs and is informed by an empirical research project. Forty families of children with Crohn's disease (CD), ulcerative colitis (UC), and functional recurrent abdominal pain syndrome (RAP) were rated during standard, videotaped family interaction tasks, lunch, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
4

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(64 citation statements)
references
References 48 publications
1
59
0
4
Order By: Relevance
“…This model was given initial research support in a study by Minuchin et al (1978), which showed a link between family interaction and blood glucose levels in certain diabetic children. Although there were methodological problems with this original study, Wood et al (1989) later found support for some elements of the psychosomatic family model, particularly triangulation and marital dysfunction, in accounting for disease activity in children with Crohn's disease.…”
Section: Systems Theories About Families and Healthmentioning
confidence: 89%
See 1 more Smart Citation
“…This model was given initial research support in a study by Minuchin et al (1978), which showed a link between family interaction and blood glucose levels in certain diabetic children. Although there were methodological problems with this original study, Wood et al (1989) later found support for some elements of the psychosomatic family model, particularly triangulation and marital dysfunction, in accounting for disease activity in children with Crohn's disease.…”
Section: Systems Theories About Families and Healthmentioning
confidence: 89%
“…Some of this activity in family therapy occurred in clinical research centers (Steinglass et al, 1982;Wood et al, 1989), and some in places where family therapists were working alongside family physicians in clinical and teaching activities (Doherty and Baird, 1983;ChristieSeely, 1984;McDaniel et al, 1990). During the 1980s, researchers such as John Gottman began programmatic investigations into the physiological aspects of marital conflict and the impact of parent distress on biological indicators such as stress hormones in children (Levenson and Gottman, 1983;Gottman and Katz, 1989).…”
Section: Historical Background and Evolution Of Medical Family Therapymentioning
confidence: 99%
“…Since the family is one of the most immediate and influential contexts for the individual, it is logical to consider family interactions as potential psychophysiological mediators or buffers of stress. Moreover, recent data show compelling correlations between stressful interpersonal relationships and physiological functioning (Gottman and Fainsilber Katz, 1989;Tarrier et al, 1988;Wood et al, 1989). None the less, despite mounting evidence for such correlation, the pathways by which this may occur in families have not been investigated.…”
Section: A Biobehavioral Family Model Of the Psychobiologically Mediamentioning
confidence: 99%
“…* Triangulation is defined as ( 1) cross-generational coalitions of the child with one parent against the other, or (2) conflict detouring through joint parental focus on the child or the child's illness. Dysfunctional parental relationships are empirically associated with greater disease activity and triangulation processes (Wood et al, 1989) and with stress-related physiological arousal in the child (Gottman and Fainsilber Katz, 1989). Parental relationship dysfunction and triangulation are potentiated by and, in turn, influence patterns of proximity, hierarchy and responsivity in families.…”
Section: )mentioning
confidence: 99%
“…The goal was to ascertain how the transplantee perceived his family to function and what might be his relationship to it. 12 Of dimensions that describe family function, two span the extremes of enmeshment to disengagement and rigidity to chaos; [13][14][15][16][17] an 'ideal' balance would be where consistency and respect for individual autonomy include sufficient flexibility to allow timely adjustment of roles, interactions and boundaries. In sum, the interview aimed to assess these life-long attributes to answer the question, 'To whom does the transplant belong?…”
Section: Psychiatric Assessmentmentioning
confidence: 99%